The Role of History Lovers Community in Raising Students Historical Awareness at Senior High School 22 Bandung - Annisa’a Ambarnis; Nana Supriatna; Leli Yulifar (JPP (Jurnal Pendidikan dan Pembelajaran), 2023)
Extracurricular history activities become a forum for students to deepen their understanding and awareness of history. The general problem studied in this research is how the implementation process of extracurricular history activities at SMAN 22 Bandung to the form of historical awareness of its student members carried out by coaches and mentors. In general, this research aims to describe the form of implementation of various extracurricular history activities named Komunitas Pecinta Sejarah (KOMPAS). The subjects in this research are the coaches and students who are members of the extracurricular history. This research was studied by applying the naturalistic inquiry method with data collection techniques of observation, interviews, documentation studies and literature studies. The data analysis technique carried out consists of three stages, namely data reduction, data display, and verification. Based on the results of the study, the History Lovers Community has a variety of educational-recreative activities carried out every week as a complement to existing intracurricular activities. The skills that are successfully developed are historical thinking and public speaking so that students are able to reconstruct historical events based on their imagination well. Strong historical thinking can increase historical awareness based on the close intertwining of students' historical emotional and intellectual elements.